129k views
19 votes
Help quick enough points

Help quick enough points-example-1
User Gillonba
by
4.7k points

2 Answers

8 votes

Explanation:

F-¹ (x)

f-¹=x-7

fx=7+1

Fx = 8 is the answer

User Krishan Gupta
by
5.5k points
7 votes

Part A

Given: f(x) = x - 7

(a)

y = x - 7 [make x the subject]

x = y + 7 [this is the inverse]

f⁻¹(x) = x + 7

(b)

(f × f⁻¹)(x) = x [go right to left in such function]

f(x + 7) = x

(x - 7) + 7 = x

x = x

Part B

Given: g(x) = 12x

(a)

y = 12x [make x the subject]

x = y/12 [this is the inverse]

g⁻¹(x) = x/12

(b)

(g × g⁻¹)(x) = x [go right to left in such function]

g(x/12) = x

12x/12 = x [simplify]

x = x

User Leo Romanovsky
by
4.7k points